A better scholarly future rests on reuniting the West with the rest, the present with the past, the theory with practice. Issue 1 (1st January 2021) - Erk, Jan
ABSTRACT: Holism, i.e. the unity of theoretical and applied reality across disciplinary demarcations, is the main leitmotiv here. The scholarly disciplines of political science, law, sociology, philosophy, anthropology, and history provide the context for the discussion. The only realistic way to understand, explain, and address global challenges is to think beyond the existing scholarly divides within academia. In the course of the discussion, scholasticism and methodological perfectionism come under fire – not only as unintended façades for Western ethnocentrism, but also as the source of reform policies and prescriptions which tend to rest on partial (and often potentially misleading) diagnoses. The argument is that only when the analysis is holistic, is the diagnosis more accurate and the prescription effective. The article calls for a cross-disciplinary perspective of an integrated, interconnected, complex whole in order to, first, better understand and explain, and then secondly, to successfully address the attending applied challenges.